The Language Observatory Project (LOP) - Mikami, Yoshiki; Pavol, Zavarsky; Abd. Rozan, Mohd. Zaidi; Suzuki, Izumi; Takahashi, Masayuki; Maki, Tomohide; Ayob, Irwan Nizan; Massimo, Santini; Boldi, Paolo; Sebastiano, Vigna (2005)
The first part of the paper provides a brief description of the Language Observatory Project (LOP) and highlights the major technical difficulties to be challenged. The latter part gives how we responded to these difficulties by adopting UbiCrawler as a data collecting engine for the project. An interactive collaboration between the two groups is producing quite satisfactory results.